Regenerative documentary posthuman art in the context of the Philippine drug war - Arumpac, Adjani Guerrero (2020)
Access online through this link: https://www.plarideljournal.org/article/regenerative-documentary-posthuman-art-in-the-context-of-the-philippine-drug-war
Keywords: Drug control; Posthumanism; Autopoiesis